Predictors of performance in algebra of first year college students of De La Salle Lipa - Medallon, Merlita (Talas, 2003)
The study, "Predictors in Algebra of First Year College Students at De La Salle Lipa " was conducted to identify the factors that affected the performance of first year students. Factors were grouped as student factors, home factors, teacher factors and school factors; and were identified with the use of correlation and regression analysis. Data was obtained with the use of questionnaires that were answered by first year students and their teachers in Algebra. Data from records of the Admissions Office, the Guidance Office and the Registrar's Office was also obtained.